Pengaruh Model Project Based Learning Berbasis Etnosains Tema 9 Benda-Benda di Sekitar kita terhadap Hasil Belajar Kelas V SD Negeri Ngijo 01 Gunungpati - Agata Dwi Marshella; Fine Reffiane; Eka Sari Setianingsih (STKIP Andi Matappa Pangkep, 2022)
This study aims to determine the effect of a project based learning model based on ethnoscience theme 9 objects around us on the learning outcomes of fifth grade students at SD Negeri Ngijo 01 Gunungpati. This type of research is a quantitative research type of Pre-Experimental Design in the form of One-Group Pretest-Posttest Design. The population in this study were all fifth grade students of SD Negeri Ngijo 01 Gunungpati for the academic year 2021/2022 totaling 25 students who were also the research sample. This sampling technique uses the Non Probability Sampling technique with a saturated sampling form. Based on data analysis, there is a difference between the average pretest and post-test learning outcomes. Based on the calculation obtained = 11.7659. While = 2,016. Because (11.7659) > (2,016) then is rejected. In addition, the pre-test learning outcomes obtained an average of 60.2. While the posttest learning outcomes obtained an average of 82.4. This shows an increase in learning outcomes pretest - posttest. So that the ethnoscience-based project-based learning model with the theme of 9 objects around us has an influence in improving the learning outcomes of fifth grade students at SD Negeri Ngijo 01 Gunungpati.